Pengembangan Aplikasi Pembelajaran Pengelolaan Sampah Daur Ulang Dengan Menggunakan IBM Cognitive Service Dan Youtube Api Berbasis Android - Andri Suranta Ginting; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the year 2018, the Malang region has produced 659,88 tonnes of waste on a daily basis and the rate gradually increases directly proportional to the number of the local population. Indonesia is ranked the second biggest contributor to the amount of plastic waste produced worldwide, second to China. Plastic waste is usually managed by means of burning, but this leads to fumes that are harmful to humans and wildlife. This research aims to apply a IBM Cognitive Service that able to analyze objects to manage recyclable waste using image recognitions technology. IBM Cognitive Service has ability to caption images with an accuracy rate of 89%. This application uses YouTube API to show users on how to manage recycable waste and to support a content search feature and a playlist that is integrated with IBM Watson Visual Recognitions which has the ability to analyze objects. The testing methods used by this application development is called SUS (System Usability Scale) which uses 10 question to measure the score, whitebox testing method, and blackbox testing method. The results from System Usability Scale (SUS) measure at 79.5. This shows that the application is categorized as acceptable in acceptable ranges, categorized with a B grade in grade scales, and categorized as good in an adjective rating. The results from the whitebox and blackbox testing methods are deemed valid, because they have fulfilled the necessary requirements.